Asistensi Mengajar di Yayasan Sulamuttarbiyah Barito Kuala - Amirul Azis Anshari Muda; Aulia Ahmad Fauzi Noor; Dina Selvia; Muhammad Andrean Lazuardi; Muhammad Choirul Hadi Santoso; Nana Fitriani; Siti Aisyah; Syah Warunadwipa Andiantosa (Carmin: Journal of Community Service, 2021)
The objectives of the program "Merdeka Learning Merdeka Campus" are to provide opportunities for students who have an interest in education, to participate in conveying their knowledge, to deepen their understanding of science itself, to participate in efforts to equalize the quality of education and to support the relevance of basic education and education. Secondary education with higher education, and the times. This activity is carried out for approximately 45 days that supports students in implementing the Merdeka Learning program at the Merdeka Campus to be directly involved in the real world. In this activity, students help teachers teach, assist school administrators, and help complete teaching facilities. Then from the results of this experience, the author can conclude that this program is very helpful for teachers or schools, where this program is useful and also beneficial for students.